Assessment of the use of ICT by distance learning students in the University of Ibadan, Nigeria (2019)
This paper reviews the use of Information and Communication Technology (ICT) by students of Distance Learning Centre, University of Ibadan, Nigeria. There is no doubt that ICT is playing a vital role in Open and Distance Learning (ODL) in terms of enhancing the provision of immediate assistant to the learners for their academic and administrative needs in large scale. It has been established that services cannot be performed in distance learning centres using traditional institutional system all alone. Therefore, ICT tools application has been incorporated to meeting the requirements of learners at various phases of learning cycle viz the admission phase and other services. The heterogeneous requirements in open distance learning has culminated into issues and challenges needed to be addressed in usage of the technologies and the service(s) being provided through ICT. Survey research design with the aid of questionnaire was employed to elicit response from the respondents. Simple random sampling technique was used to select the sample size of this work. The effectiveness, stimulating factors, issues and challenges confronting ICT usage, purpose as well as other challenges encountered by staff and students of University of Ibadan DLC were emphasised. Recommendations were made based on the findings.